Saudi Arabia’s Green Vision: Examining the Kingdom’s Path to Sustainability, Covering Energy, Economy, Tourism, and Carbon Dynamics - Faisal, Shaha; Khan, Aarif Mohammad; Zulfikar, Zehra; Bafaqeer, Salim M. (International Journal of Energy Economics and Policy, 2024)
This study examines the Green Vision of Saudi Arabia and its efforts towards achieving sustainability in various domains such as energy, economy, tourism, and carbon emissions. The research uses time-series data from 2002 to 2020 to analyze the dynamic impacts of these variables. To achieve this, it employs a co-integration regression test, Granger causality relationships, and one-way and two-way causal effects between carbon emissions, tourism, economic growth, and energy use. The findings of the study provide valuable insights into the challenges and opportunities for sustainability in the kingdom, considering the goals of SDGs 8 and 13. This research contributes to the ongoing discourse on sustainable development in Saudi Arabia and offers significant insights for lawmakers, entrepreneurs, and researchers to influence the country’s future direction. The research aims to guide strategic decision-making in line with Saudi Arabia’s commitment to achieving a sustainable and resilient future by examining the interconnections between energy, economic growth, tourism, and carbon emissions.